Study of significance of elevated maternal serum β-human chorionic gonadotropin (β-hCG) level in 16 to 20 weeks pregnant women as predictor of hypertensive disorder of pregnancy - Pawar, Preeti; Goyal, Ritu; Kaur, Harvinder; Singal, Neelam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hypertensive disorder of pregnancy affects both mother and fetus, leading their high morbidity and mortality and a major killer of women in developing country. The etiologic of preeclampsia is still not clear. It seems that placenta plays main role in path-physiology of preeclampsia, but there is strict relationship between hypertensive disorder of pregnancy and elevated β-hCG level, indicating there should be an abnormal placental secretary function in patients with severe preeclampsia. Methods: 245 patients were recruited from our institute (OPD) and Prospective analytical study was started with 16-20 weeks pregnant women. Cases were subjected to detailed history and thorough physical examination including baseline blood pressure. β-hCG measurement was done between 16-20 weeks and cases were followed at regular interval for the development of hypertensive disorder of pregnancy. Statistical testing was conducted with appropriate tests. Results: Total 245 women were enrolled in the study, only 208 were followed till delivery, 24 were developed hypertension. On analysis of data, maximum cases were younger, primigravida and of lower class. β-hCG levels (Mean ± SD) were also significantly higher (30100±16250 V/S 74700±23790; p<0.001) in subjects who later developed hypertension. Cut off value of β-hCG was 45755 mIU/ml, and analysis establishes validity of β-hCG as predictor of hypertensive disorder of pregnancy with sensitivity, specificity, positive and negative predictive value for β hCG were 87.5, 83.2, 70.4 and 83.7% respectively. Conclusions: Present study shows that elevated serum β-hCG in early second trimester can be considered as predictor of subsequent hypertensive disorder of pregnancy.